2016
DOI: 10.1007/s00228-016-2091-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hypernatremia in patients with short- and long-term tolvaptan treatment

Abstract: A daily dosage of 7.5 mg or less was recommended to prevent hypernatremia in short- as well as long-term tolvaptan treatment, and mainly elderly patients were at risk for hypernatremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
0
25
6
Order By: Relevance
“…In recent years, they, in particular tolvaptan, have assumed major importance compared with conventional therapeutic approaches (water restriction or 3% hypertonic saline solution) for the treatment of hyponatremia [21,22,23,24,25,26,27] (see also Table 2). In Table 3, Table 4, Table 5 and Table 6, some characteristics of VRAs are outlined.…”
Section: The Vasopressin Receptor Antagonists (Vras): Promoting Frmentioning
confidence: 99%
“…In recent years, they, in particular tolvaptan, have assumed major importance compared with conventional therapeutic approaches (water restriction or 3% hypertonic saline solution) for the treatment of hyponatremia [21,22,23,24,25,26,27] (see also Table 2). In Table 3, Table 4, Table 5 and Table 6, some characteristics of VRAs are outlined.…”
Section: The Vasopressin Receptor Antagonists (Vras): Promoting Frmentioning
confidence: 99%
“…Serum potassium concentration was not found to be a risk factor in the study of Hirai et al 14 This difference could be attributed to the patient mix, because Hirai et al 14 included patients with liver cirrhosis in their study. The…”
Section: Discussionmentioning
confidence: 89%
“…Tolvaptan potentially causes severe hypernatraemia at therapeutic doses. 5 Our data revealed that the CYP3A5*3 allele raised the plasma tolvaptan concentration. The effect of tolvaptan on serum sodium usually appeared within 5 days after starting the medication.…”
Section: Discussionmentioning
confidence: 50%
“…3 Adverse effects such as severe hypernatraemia and potentially fatal liver injury were reported in clinical settings. 4,5 However, tolvaptan plasma exposure itself has not fully explained the efficacy and safety. 6 Tolvaptan is mainly converted to three monohydroxylates (DM-4110, DM-4111 and DM-4119) and a ring-opened carboxylate (DM-4103) in the human liver ( Figure S1).…”
Section: Introductionmentioning
confidence: 99%